Studien zum Grab 111 der Nekropole von Fuente Álamo (Almería) - Schubart, Hermanfrid; Pingel, Volker; Kunter, Manfred; Liesau von Lettow-Vorbeck, Corina; Pozo, Manuel; Medina , José Antonio; Casas, José; Juan i Tresseras, Jordi; Hägg, Inga (Madrider Mitteilungen, 2020)
Deutsche Zusammenfassung folgt.